2018
DOI: 10.1098/rsbl.2018.0360
|View full text |Cite
|
Sign up to set email alerts
|

Water for African elephants ( Loxodonta africana ): faecal microbial loads affect use of artificial waterholes

Abstract: In semi-arid protected areas, artificial waterholes ensure that water is locally available to animals for extended periods. However, artificial waterholes may limit animal movement, which contributes towards habitat deterioration. Challenges of artificial water provisioning worsen in the presence of ecosystem engineers like African elephants , capable of transforming environments. Camera traps were used to monitor elephant visitation at 21 artificial waterholes in the Kruger National Park, South Africa. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Parasite avoidance behavior may complicate our findings if animals can detect parasites in water or the environment. For example, other studies have shown fecal avoidance in feeding dik-dik (a small antelope) 47 and elephants and lemurs seeking water 62 , 63 . These studies suggest that in certain cases, the costs of parasite exposure may alter animal behavior and foraging.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite avoidance behavior may complicate our findings if animals can detect parasites in water or the environment. For example, other studies have shown fecal avoidance in feeding dik-dik (a small antelope) 47 and elephants and lemurs seeking water 62 , 63 . These studies suggest that in certain cases, the costs of parasite exposure may alter animal behavior and foraging.…”
Section: Discussionmentioning
confidence: 99%
“…Among substrates known to harbour infectious agents, faeces are known to elicit avoidance behaviour in a wide range of animal species, including insects [8], rodents [9], ungulates [10], marsupials [11] and proboscids [12]. This is for good reason, as a multitude of infectious organisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding factors that influence spatial heterogeneity in megaherbivore distribution and effects on vegetation has been an important goal for ecologists. However, many studies have either focused on large‐scale patterns across large altitudinal gradients, different vegetation zones, and different rainfall regimes (Bell, 1982; Bohrer, Beck, Ngene, Skidmore, & Douglas‐Hamilton, 2014; Fritz & Duncan, 1994; Holdo, 2003; Howes, Doughty, & Thompson, 2019; Mysterud, Langvatn, Yoccoz, & Nils Chr, 2001; Ngene, Skidmore, Van Gils, Douglas‐Hamilton, & Omondi, 2009), or patterns associated with proximity to focal points such as surface water sources (Chamaillé‐Jammes, Mtare, Makuwe, & Fritz, 2013a; Ndlovu et al., 2018; Wato et al., 2018), human settlements (Neupane, Kwon, Risch, Williams, & Johnson, 2019), and roads (Gaynor et al., 2018), but see (Bond & Loffell, 2001; Coetsee & Wigley, 2016). Consequently, we know little about how fine‐scale habitat patch characteristics such as local variation in topography and edaphic‐driven contrasts in vegetation structure and resource densities may influence megaherbivore effects on vegetation.…”
Section: Introductionmentioning
confidence: 99%